Construction of occluded recombinant baculoviruses containing the full-length cry1Ab and cry1Ac genes from Bacillus thuringiensis - Ribeiro,B.M. (1998)
The administration of baculoviruses to insects for bioassay purposes is carried out, in most cases, by contamination of food surfaces with a known amount of occlusion bodies (OBs). Since per os infection is the natural route of infection, occluded recombinant viruses containing crystal protein genes (cry1Ab and cry1Ac) from Bacillus thuringiensis were constructed for comparison with the baculovirus prototype Autographa californica nucleopolyhedrovirus (AcNPV). The transfer vector pAcUW2B was used for construction of occluded recombinant viruses. The transfer vector containing the crystal protein genes was cotransfected with linearized DNA from a non-occluded recombinant virus. The isolation of recombinant viruses was greatly facilitated by the reduction of background "wild type" virus and the increased proportion of recombinant viruses. Since the recombinant viruses containing full-length and truncated forms of the crystal protein genes did not seem to improve the pathogenicity of the recombinant viruses when compared with the wild type AcNPV, and in order to compare expression levels of the full-length crystal proteins produced by non-occluded and occluded recombinant viruses the full-length cry1Ab and cry1Ac genes were chosen for construction of occluded recombinant viruses. The recombinant viruses containing full-length and truncated forms of the crystal protein genes did not seem to improve its pathogenicity but the size of the larvae infected with the recombinant viruses was significantly smaller than that of larvae infected with the wild type virus.